IMPLEMENTATION OF RELIGIOUS VALUES THROUGH DHUHA PRAYER AND TAHFIDZ ALQUR`AN ACTIVITIES IN CHILDREN - Samsul Fajeri; Husin; Siti Khadijah; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Religious education aims to increase religious potential and shape children to become human beings who believe in and fear God Almighty and have noble character which includes ethics, character and morals. Religious value in children is a child's ability to understand religion that is obtained from parents, society and the surrounding environment. One of the efforts that can be made to achieve children with religious character is to instill religious values ​​themselves in children through religious activities such as the habit of praying dhuha in congregation and tahfiz Al-Qur`an activities both starting from the school environment. This study aims to instill religious values ​​in children which must be instilled since childhood, so that children get used to behaving well towards other people in their surroundings and have a love for the Al-Qur`an which increases their faith and piety to God Almighty. This research was conducted at the Subsidized Muhammadiyah Elementary School in Galagah Hulu. This study uses a descriptive qualitative research method in which data collection uses observation techniques, interview techniques and documentation techniques. The results of this study indicate that in the habituation of Duha prayer carried out by children in congregation, they find several religious values, namely the value of worship, the value of spirit of jihad, moral values ​​and exemplary values. Strategies in instilling religious values ​​by motivating and setting an example. One way to instill religious values ​​is to always keep the Duha prayer time. tells the virtues of dhuha prayer, tells the virtues of memorizing the Qur'an in life so as to foster a sense of love in children. In the activities of tahfidz Al-Qur`an the religious values ​​found are children who are used to being disciplined in carrying out activities to memorize surahs while at school, children are disciplined in obeying school rules. The conclusion of this study is that through the habit of praying Dhuha in congregation and tahfidz Al-Qur`an religious values ​​can be fostered which are reflected in good attitudes, behavior and personality in everyday life. Discipline in obeying school rules. The conclusion of this study is that through the habit of praying Dhuha in congregation and tahfidz Al-Qur`an religious values ​​can be fostered which are reflected in good attitudes, behavior and personality in everyday life. Discipline in obeying school rules. The conclusion of this study is that through the habit of praying Dhuha in congregation and tahfidz Al-Qur`an religious values ​​can be fostered which are reflected in good attitudes, behavior and personality in everyday life.